Mechanical characterization of different epoxy resins enhanced with carbon nanofibers (Fracture and Structural Integrity, 2020)
Epoxy with carbon nanofibers (CNFs) are effective nano enhanced materials that can be prepared by easy and low-cost method. The present paper compares the improvements, in terms of flexural and viscoelastic properties, of two epoxy resins reinforced with different weight percentages (wt.%) of CNFs. These epoxy resins have different viscosities, and weight contents between 0% and 1% of CNFs were used to achieve the maximum mechanical properties. Subsequently, for the best configurations obtained, the sensitivity to the strain rate and the viscoelastic behaviour (stress relaxation and creep) were analysed based on international standards. It was possible to conclude that, for both resins, carbon CNFs promote significant improvements in all the studied mechanical properties, even for different contents by weight.
Keywords: Composites; Epoxy resins; Carbon nanofibers; Mechanical properties